2013
DOI: 10.1111/hdi.12040
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐to‐lymphocyte ratio better predicts inflammation than neutrophil‐to‐lymphocyte ratio in end‐stage renal disease patients

Abstract: Neutrophil-to-lymphocyte ratio (NLR) was introduced as a potential marker to determine inflammation in end-stage renal disease (ESRD) patients. Recently, platelet-to-lymphocyte ratio (PLR) and NLR were found to positively correlated with inflammatory markers including tumor necrosis factor-α (TNF-α) and interleukin (IL)-6 in cardiac and noncardiac patients. Data regarding PLR and its association with inflammation are lacking in hemodialysis (HD) and peritoneal dialysis (PD) patients. Hence, we aimed to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
198
3
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(234 citation statements)
references
References 28 publications
16
198
3
14
Order By: Relevance
“…[21][22][23] However, we did not find use of these parameters for determining prognosis in cases of FG in the English literature. In our study, we identified strong correlations between these parameters and the prognosis of the disease.…”
Section: Discussionmentioning
confidence: 74%
“…[21][22][23] However, we did not find use of these parameters for determining prognosis in cases of FG in the English literature. In our study, we identified strong correlations between these parameters and the prognosis of the disease.…”
Section: Discussionmentioning
confidence: 74%
“…There are valuable results in the studies about the role of PLR in terms of prognosis of the patients with breast and gynaecological malignancies 12,13,20,21 . The predictive values of PLR in patients with myocardial infarction, peripheral arterial occlusive disease, and end-stage renal diseases were also studied [22][23][24] . But we didn't find any study about PLR and AA in English Literature.…”
Section: Resultsmentioning
confidence: 99%
“…In the study of Turkmen et al (2013), has been indicated that PLR may better predict the infl ammation than NLR in the end stage of the renal disease. However, in our study, both NLR and PLR were better than CRP but NLR was also better than PLR.…”
Section: Discussionmentioning
confidence: 99%